2019
DOI: 10.1021/acsnano.8b07677
|View full text |Cite
|
Sign up to set email alerts
|

Stark Effect and Environment-Induced Modulation of Emission in Single Halide Perovskite Nanocrystals

Abstract: Organic–inorganic halide perovskites have emerged as promising materials for next-generation solar cells. In nanostructured form also, these materials are excellent candidates for optoelectronic applications such as lasers and light-emitting diodes for displays and lighting. While great progress has been achieved so far in optimizing the intrinsic photophysical properties of perovskite nanocrystals (NCs), in working optoelectronic devices, external factors, such as the effects of conducting environment and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 56 publications
2
45
0
Order By: Relevance
“…Some aggregates are more intense in PL (e.g., the one denoted by blue circles) while others are more intense in EL (red circles) and some aggregates appear only in one of the images. Compared to single NCs which have been reported to exhibit strong PL blinking in PVK matrix before 37 (such as the one shown in Fig. 1e), most of the NC aggregates do not show any blinking in PL due to the intra-aggregate ensemble averaging (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…Some aggregates are more intense in PL (e.g., the one denoted by blue circles) while others are more intense in EL (red circles) and some aggregates appear only in one of the images. Compared to single NCs which have been reported to exhibit strong PL blinking in PVK matrix before 37 (such as the one shown in Fig. 1e), most of the NC aggregates do not show any blinking in PL due to the intra-aggregate ensemble averaging (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…Single-photon emission from single perovskite CsPbX 3 NCs was reported by Park et al 123 At the same time, single-photon emission and the associated fluorescence blinking were also reported by Hu et al 125 in single CsPbBr 3 NCs, which additionally demonstrated several superior optical properties such as a large absorption cross section, a fast radiative lifetime, and a suppressed dark-exciton emission. Sharma et al 126 later discovered that the optical and chemical properties of single CsPbBr 3 NCs could be strongly influenced by the surrounding polymers, thus suggesting an alternative way of adjusting their relative energy-level alignments for a full suppression of the fluorescence blinking effect. Surprisingly, Hu et al 124 later discovered that the fluorescence blinking behavior was completely missing in single CsPbI 3 NCs under low-power laser excitation, as can be seen from the PL intensity time trace plotted in Fig.…”
Section: Single-photon Emission Characteristicsmentioning
confidence: 99%
“…Ideas along these lines have been used to speculate about the nature of EF-dependent luminescence blinking of perovskite quantum dots and individual molecules of conjugated polymers. [49,50] In contrast, when the alternating EF with high frequency was applied to the samples of both MAPbI 3 and MAPbBr 3 , the internal field was about one order of magnitude higher than for the constant EF condition. Strong EF induces separation of electron and holes and also pulls apart ions of the opposite sign.…”
Section: Possible Mechanisms Of Pl Response Of Mapbx 3 Polycrystals Tmentioning
confidence: 99%